Femtoscopy of pp collisions at √s=0.9 and 7 TeV at the LHC with two-pion Bose-Einstein correlations - Aamodt, Kenneth; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Lohner, Daniel; Lu, Xianguo; Mercado Pérez, Jorge; Oyama, Ken; Pachmayer, Yvonne C.; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We report on the high statistics two-pion correlation functions from pp collisions at √s=0.9 TeV and √s=7 TeV, measured by the ALICE experiment at the Large Hadron Collider. The correlation functions as well as the extracted source radii scale with event multiplicity and pair momentum. When analyzed in the same multiplicity and pair transverse momentum range, the correlation is similar at the two collision energies. A three-dimensional femtoscopic analysis shows an increase of the emission zone with increasing event multiplicity as well as decreasing homogeneity lengths with increasing transverse momentum. The latter trend gets more pronounced as multiplicity increases. This suggests the development of space-momentum correlations, at least for collisions producing a high multiplicity of particles. We consider these trends in the context of previous femtoscopic studies in high-energy hadron and heavy-ion collisions and discuss possible underlying physics mechanisms. Detailed analysis of the correlation reveals an exponential shape in the outward and longitudinal directions, while the sideward remains a Gaussian. This is interpreted as a result of a significant contribution of strongly decaying resonances to the emission region shape. Significant nonfemtoscopic correlations are observed, and are argued to be the consequence of “mini-jet”-like structures extending to low pt. They are well reproduced by the Monte-Carlo generators and seen also in π+π− correlations.